Odpowiedzi

2010-02-25T18:47:19+01:00
Wyłącz przed nawias:
a) 2x(1-y)
b)2x(2-4y)
c)2x(3x-6)

Przedstaw w postaci iloczynu:
a)5x2-15x = 5x(x-3)
b)3by-6b = 3b(y-2)
c)-8xy+8x = 8x(-y+1)
d)10a2-2ab = 2a(5a-b)
e)xy-x2y = xy(1-x)
f)6a-24b+30b = 6(a-4b+5b)
g)12ab2+16b2 = 4b2(3a+4)
h)x3-2x2+x = x(x2-2x+1)
i)2xy+3x-x2y = x(2y+3-xy)
155 2 155
Najlepsza Odpowiedź!
2010-02-25T18:51:59+01:00
A) 2x-2xy = 2x(1-y)
b) 4x-8xy = 2x(2-4y)
c)6x2-12x = 2x(3x-6)
Przedstaw w postaci iloczynu:
a)5x2-15x = 5x(x-3)
b)3by-6b = 3b(y-2)
c)-8xy+8x = 8x(-y+1)
d)10a2-2ab = 2a(5a-b)
e)xy-x2y = xy(1-x)
f)6a-24b+30b = 6(a-4b+5b)
g)12ab2+16b2 = 4b2(3a+4)
h)x3-2x2+x = x(x2-2x+1)
i)2xy+3x-x2y = x(2y+3-xy)


Liczę na naj ;)
47 4 47
2010-02-25T18:54:34+01:00
A) 2x-2xy=2x(1-y)
b) 4x-8xy=2x(2-4y)
c)6x2-12x=2x(3x-6)


a)5x2-15x=5x(x-3)
b)3by-6b=3b(y-2)
c)-8xy+8x=8x(-y+1)=8x(1-y)
d)10a2-2ab=2a(5a-b)
e)xy-x2y=xy(1-x)
f)6a-24b+30b=6a+6b=6(a+b)
g)12ab2+16b2=4b2(3a+4)
h)x3-2x2+x=x(x2-2x+1)
i)2xy+3x-x2y=x(2y+3-xy)
35 2 35